Effect of NAMPT on the proliferation and apoptosis in odontoblast-like MDPC-23 cell: Effect of NAMPT on MDPC-23 cell survival - Kang, Kyeong-Rok; Park, Joo-Cheol; Kim, Chun Sung; Kim, Heung-Joong; Yu, Sun-Kyoung; Chun, Hong Sung; Lim, HyangI; Seo, Jeong-Yeon; Kim, Jae-Sung; Kim, Do Kyung (Cellular and Molecular Biology, 2024)
This study aimed to evaluate the physiological role of NAMPT associated with MDPC-23 odontoblast cell proliferation. Cell viability was measured using the (DAPI) staining, caspase activation analysis and immunoblotting were performed. Visfatin promoted MDPC-23 odontoblast cell growth in a dose-dependent manner. Furthermore, the up-regulation of Visfatin promoted odontogenic differentiation and accelerated mineralization through an increase in representative odontoblastic biomarkers in MDPC-23 cells. However, FK-866 cell growth in a dose-dependent manner induced nuclear condensation and fragmentation. FK-866-treated cells showed H&E staining and increased apoptosis compared to control cells. The expression of anti-apoptotic factors components of the mitochondria-dependent intrinsic apoptotic pathway significantly decreased following FK-866 treatment. The expression of pro-apoptotic increased upon FK-866 treatment. In addition, FK-866 activated caspase-3 and PARP to induce cell death. In addition, after treating FK-866 for 72 h, the 3/7 activity of MDPC-23 cells increased in a concentration-dependent manner, and the IHC results also confirmed that Caspase-3 increased in a concentration-dependent. Therefore, the presence or absence of NAMPT expression in dentin cells was closely related to cell proliferation and formation of extracellular substrates.